Tenancy Reform in India P.S. Appu. - Planning Commission (Planning Commission, 1975)
Recent years have witnessed a revival of public interest in land reform. This renewed interest is, however, largely confined to the question of calling on agricultural holdings. In a predominantly agrarian economy the salient features of which are a very high man-land ratio, unequal distribution of holdings, scarcity of capital and slow growth of non-farm employment, the relevance of a policy of radical re-distribution of land is obvious.
Planning Commission
Planning Commission